A new endemic Vincetoxicum (Apocynaceae) in the Eastern Cape, and a conspectus of the genus for South Africa - Meve, Ulrich; Heiduk, Annemarie; Liede-Schumann, Sigrid (Phytotaxa, 2020)
A new species is described in African Vincetoxicum (incl. Tylophora), and the present status of Vincetoxicum in South Africa is recapitulated. The new species, here described as Vincetoxicum stylesii, is a twining forest dweller known so far only from the Dwesa-Cwebe Nature Reserve in the Eastern Cape Province of South Africa. Due to its isolated phylogenetic position at the very base of Vincetoxicum, and to its rarity, it is to be regarded as a relict species. With the new species, the genus includes ten species in South Africa when adopting the here also proposed new synonymy for Vincetoxicum simianum (in V. cordatum) and V. badium var. latifolium (in V. umbelliferum); six of the species are endemic.